The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1143/jjap.46.2799
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Modulated Assembly of Magnetized Iron-Filled Carbon Nanotubes in Millimeter-Scale Structures

Abstract: Biomolecule-functionalized carbon nanotubes (CNTs) combine the molecular recognition properties of biomaterials with the electrical properties of nanoscale solid state transducers. Application of this hybrid material in bioelectronic devices requires the development of methods for the reproducible self-assembly of CNTs into higher-order structures in an aqueous environment. To this end, we have studied pattern formation of lipid-coated Fe-filled CNTs, with lengths in the 1-5 mm range, by controlled evaporation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…The observation of a cylindrical micelle of lipids surrounding a CNT is of interest, suggesting that lipids may be used to solubilize CNTs. This is supported by recent experiments on (derivatized) CNTs which suggest solubilization by lipids may indeed be possible [33].…”
Section: Discussionsupporting
confidence: 69%
“…The observation of a cylindrical micelle of lipids surrounding a CNT is of interest, suggesting that lipids may be used to solubilize CNTs. This is supported by recent experiments on (derivatized) CNTs which suggest solubilization by lipids may indeed be possible [33].…”
Section: Discussionsupporting
confidence: 69%
“…To enhance the magnetic susceptibility of CNTs, some researchers strategically incorporated paramagnetic or ferromagnetic materials using various chemical and physical methods as reviewed by Samouhos and McKinley [78]. Toledo and co-workers [24], for example, studied pattern formation during the drying of an aqueous CNT/lipid suspension and showed that aggregate structures were altered in the presence of a magnetic field.…”
Section: Magnetic Fieldmentioning
confidence: 99%
“…Other characterization techniques reported in the literature include polarized Raman microscopy [81][82][83], X-ray diffraction [84,85], near-infrared fluorescence microscopy [86], and tagging CNTs with fluorescent markers [87][88][89][90]. Besides in situ characterization, the orientation distribution of CNTs can also be characterized indirectly by performing electron microscopy on extruded or cured samples (see, for example, references [24], [47], [91], and [92]).…”
Section: Characterization Of Cnt Orientationmentioning
confidence: 99%